Pengaruh Price, Wom (Word Of Mouth) Dan Brand Trust Terhadap Keputusan Pembelian Tiket Bus Juragan 99 (Studi Pada Penumpang Bus Juragan 99 Rute Malang-Jakarta) - Arifin, Khoirul; Widarko, Agus; Slamet, Afi Rahmat (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research uses quantitative methods or also called explanatory research. The population used probability sampling techniques. The sample used was purposive sampling and used the Slovin measurement technique with a sample size of 99. The data source used was primary data obtained by distributing questionnaires to responden. The data analysis method used is multiple linier regression analysis. The research results show that simultaneously or partially, the variable price, word of mouth and brand trust have a significant effect on purchasing decisions. Keywords: Price, Word Of Mouth And Brand Trust, Purchasing Decisions.